Fresh-blood-free diet for rearing malaria mosquito vectors - Marques, Joana (2019)
Mosquito breeding depends on the supply of fresh vertebrate blood, a major bottleneck for large-scale production of Anopheles spp. Feeding alternatives to fresh blood are thus a priority for research, outdoor large-cage trials and control interventions. Several artificial meal compositions were tested and Anopheles oogenesis, egg laying and development into the next generation of adult mosquitoes were followed. We identified blood-substitute-diets that supported ovarian development, egg maturation and fertility as well as, low progeny larval mortality, and normal development of offspring into adult mosquitoes. The formulated diet is an effective artificial meal, free of fresh blood that mimics a vertebrate blood meal and represents an important advance for the sustainability of Anopheles mosquito rearing in captivity.